Development and pilot testing of an online monitoring tool of depression symptoms and side effects for young people being treated for depression. Issue 1 (25th February 2014) - Hetrick, Sarah E.; Dellosa, Maria Kristina; Simmons, Magenta B.; Phillips, Lisa
Abstract Aim To develop and examine the feasibility of an online monitoring tool of depressive symptoms, suicidality and side effects. Methods The online tool was developed based on guideline recommendations, and employed already validated and widely used measures. Quantitative data about its use, and qualitative information on its functionality and usefulness were collected from surveys, a focus group and individual interviews. Results Fifteen young people completed the tool between 1 and 12 times, and reported it was easy to use. Clinicians suggested it was too long and could be completed in the waiting room to lessen impact on session time. Overall, clients and clinicians who used the tool found it useful. Conclusions Results show that an online monitoring tool is potentially useful as a systematic means for monitoring symptoms, but further research is needed including how to embed the tool within clinical practice.